Hyperkalemia - a review article - Marcin Makuch; Marcelina Makuch; Kamila Tuzim (Kazimierz Wielki University, 2019)
Introduction: Potassium is critical cation in physiological functions. Hyperkalemia is a common electrolyte disorder, defined as potassium level above 5,5 mmol/L. Knowledge of the basic rules of hyperkalemia management is crucial to every doctor. Purpose: Systemic review of causes, symptoms and treatment of hyperkalemia. Material and methods: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out. Description of the state of knowledge: The causes of hyperkalemia are different and mostly result from impaired urinary potassium excretion due to acute or chronic kidney disease. The symptoms of hyperkalemia vary and usually affect skeletal muscles, myocardium and central nervous system. Treatment of hyperkalemia depends on the presence or absence of symptoms, the severity of potassium elevation and the cause of hyperkalemia. Therefore, management with the patient with hyperkalemia includes careful interview, evaluation of clinical symptoms, ECG and searching for possible causes of disorders. Summary: Hyperkalemia requires urgent therapeutic intervention. In each case of elevated potassium concentration ECG should be performed and the obtained laboratory result should be verified. The crucial point in hyperkalemia treatment is the shift of potassium to the cells and simultaneously the removal of potassium from the body.